PENGARUH MEDIA POP-UP BOOK TERHADAP KETEPATAN URUTAN WUDU ANAK USIA DINI DI RAUDHATUL ATHFAL NURUL IMAN PADANG - Wasipa Shuhra; Syahrul Ismet; Dadan Suryana; Asdi Wirman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low proficiency of early childhood students at Raudhatul Athfal Nurul Iman Padang in performing the ablution sequence correctly. The learning process was still dominated by conventional media, causing children to struggle with understanding the sequential steps of abulation. This study aimed to determine the effect of using pop-up book media on the accuracy of the abulation sequence among early childhood students. A quantitative approach using a quasi-experimental method was employed. The study population consisted of 105 children from Group B, while the sample comprised 24 children selected via purposive sampling and divided into experimental and control groups. Data were collected through practical tests and analyzed using normality tests, homogeneity tests, gain scores, and independent sample t-tests with the aid of SPSS. The results showed that the average post-test score for the experimental group 15.00 was higher than that of the control group 12.25 Hypothesis testing revealed a significance value of 0.000(<0.05), indicating that the use of pop-up book media had a significant effect on the accuracy of the abulation sequence among early childhood students. Thus, pop-up book media can serve as an innovative learning alternative to enhance the development of religious and moral values ​​in early childhood.